Sustaining pedagogical mentoring: Insights from English as a Foreign Language teachers’ experiences and needs - Lap, Trinh Quoc; Vy, Phan Ngoc Tuong; Tuan, Le Cong; Nga, Ngo Huynh Hong; Tai, Huynh Ngoc (International Journal of Innovative Research and Scientific Studies, 2025)
Mentoring plays a vital role in the professional development of in-service EFL teachers in both professional and well-being aspects. While international research has investigated diverse mentoring models and their impact on teacher development, mentoring practices in Vietnam, particularly in high schools, remain underexplored. As change agents, EFL teachers should be equipped with qualified mentoring programs to exude their agency in the evolving context of English Language Teaching (ELT). This study investigated (1) in-service EFL teachers’ evaluations of the quality of mentoring activities delivered by EFL trainers in the scope of an ELT innovation project in Vietnam, and (2) their expectations for sustaining the quality of mentoring activities. Conducted in the underdeveloped areas around the Mekong Delta of Vietnam, the study adopted a mixed-method approach, involving 273 survey respondents and 12 interview participants. Results indicate that teachers value mentors’ professional expertise and social skills yet express the need for more practice-oriented mentoring and emotionally driven communication, especially in reverse intergenerational mentor-mentee relationships. Findings indicated the importance of refining mentoring programs to create harmony between innovative and traditional ELT methodologies. Ultimately, these findings contribute to maintaining and reinforcing the sustainability of mentoring activities in the field of ELT.